Implementation of Corn Sale And Purchase Agreement Law For Farmers With A Partnership Wholesale Transaction System: A Study on Brata Rumbia Trading Business In Central Lampung - Meida Anggi Fahira (NEGREI: Academic Journal of Law and Governance, 2024)
This study discusses the implementation of the law of corn sale and purchase agreements carried out by farmers with a wholesale transaction system through the Brata Rumbia trading business partnership in Central Lampung. The focus of the study is on the implementation of the agreement, compliance with civil law provisions, and its impact on the parties involved. The research method used is a juridical-empirical approach, namely by reviewing the agreement documents and their implementation in the field through interviews with farmers and Brata Rumbia. The results of the study indicate that this wholesale transaction system involves a partnership agreement that includes the terms of sale and purchase, the agreed price, and the rights and obligations of each party. However, several obstacles were found such as the discrepancy between the harvest results and the initial agreement, farmers' dependence on partners, and farmers' minimal understanding of the contents of the agreement. This has the potential to cause injustice to farmers. In conclusion, although the agreement is in principle in accordance with civil law, its implementation requires further supervision to ensure justice for all parties. Recommendations submitted include increasing farmers' legal literacy and stricter supervision from related parties.